Ultrasound Assessment of Cesarean Section Scar and its Correlation to Intraoperative Scar Status - Saba Pario, Sanober Omer, Sughra Abbasi, Anam Pario, Sadia Suboohi, Ramla Javed Baig, (Pakistan Journal of Medical & Health Sciences, 2022)
Background and Aim: In the past decades the rate of cesarean sections has increased enormously, there are many indications for cesarean section like placenta previa, labor dystocia, presumed fetal distress, fetal malpresentation, multiple gestation, and suspected fetal macrosomia, but the commonest reason for performing a cesarean is a previous cesarean birth .The present study aimed to compare the sonographically measured lower uterine scar with actual status of scar at the time of operation. Methodology: The descriptive cross-sectional study was conducted on 150 female patients who presented to Obstetrics department of Creek general hospital, affiliated with UMDC from August 2021 to January 2022. The Inclusion Criteria was: females with singleton pregnancy with history of previous single caesarian section, vertex presentation and gestational age 36-40 weeks. While women with multiple gestations, placenta previa, polyhydramnios or any uterine abnormality were excluded. Results: The overall mean of age, gestational age, parity and fetal weight were 28.22±4.59 years, 37.60±0.78 weeks, 1.73±0.94 and 2.75± 0.47 kg respectively. Significant association was observed between lower uterine segment measurements by Sonographic scar thickness during pregnancy and intra-operative scar findings at the time of delivery (p-value< 0.05). Conclusion: The present study found that sonographically measured lower uterine scar thickness is a solid predictor for scar defect in women with previous cesarean section. As a result, we can conclude that sonographic measurement of lower uterine segment thickness is a reliable tool for assessing scar status and deciding which women should be given a vaginal delivery trial. Keywords: Previous Caesarean Section, Lower uterine scar, Sonography